Influence of pseudoboehmite on the performance of shaped mordenite catalyst for dimethyl ether carbonylation. (15th May 2023) - Chu, Pengfei; Liu, Hu; Cai, Kai; Liu, Yunduo; Li, Ying; Wang, Yue; Wang, Shengping; Huang, Shouying; Ma, Xinbin
Highlights: The influence of pseudoboehmite on structural and acidic properties of extruded MOR were revealed. The diffusion behaviors of DME in shaped MOR were quantitatively investigated by standard and time-fractional diffusion. The enhanced mass transfer compensated the negative effects of decreased acidity in shaped MOR. Abstract: As a key step of indirect production of ethanol from syngas, the carbonylation of dimethyl ether (DME) has attracted much attention. It is of great importance to develop shaped catalyst with high efficiency and strong mechanical properties to promote the process industrialization. Extruded mordenite (MOR) has been used as the catalyst for industrial DME carbonylation. In this work, the effect of properties and content of pseudoboehmite as a binder on mechanical strength and catalytic performance of the extruded MOR were systematically studied. Combining TG, XRD, N2 adsorption, and rheological property analysis etc., we found that the interlayer water content of pseudoboehmite affect peptization process, which leads to the difference in mechanical strength and pore structure. Then, the DME carbonylation performance of the extruded MOR was discussed based on textural parameters and acidic properties. Further, DME diffusion experiments were conducted and analyzed by using standard and the time-fractional diffusion models respectively. As a result, the influence of pseudoboehmite on mass transfer performance was quantitatively analyzed. The results will provide important guidance for the development of shaped zeolite catalysts in industry.